Engineering transformations in the ‘religion-development nexus’: Islamic law, reform, and reconstruction in Aceh - Feener, R. Michael (Religion, 2021)
This article presents an exploration of the ways in which law, education, and religious propagation have been deployed as mutually reinforcing means for engineering social transformation in the Indonesian province of Aceh, and how these agendas were dramatically accelerated in the context of humanitarian and development interventions in post-conflict/post-disaster reconstruction. In doing so, it demonstrates and critically analyzes the ways in which contemporary Muslim visions of instrumentalist, future-oriented models of Islamic law have been formally implemented through the apparatus of the state as part of an over-arching project of engineering a new society, and of redefining conceptions of proper Islamic religious belief and practice. This case presents a striking instance of an agenda of religious revival envisioned not as an attempt to preserve or resuscitate established tradition, but rather as a tool in interventions for future-oriented projects for ‘improving’ the conditions of Muslims in both this world, and the next.